Análise da microbiota associada à ascídia Didemnum granulatum para a produção de metabólitos secundários bioativos - Carvalho, Erica de (2010)
Studies of marine natural products in 20 years of research have revealed a wide variety of molecules with complex structures and hitherto unknown, and potent biological activities. The aims of this study were to isolate microbial strains associated with Didemnum granulatum, to fermentate such strains for the production of crude extracts and the screening of these extracts for bioactive secondary metabolites. For the isolation of the strains, six different culture media were prepared with artificial sea water: malt extract 2% and 3%, carrot/potato, corn, oat and GPY. The strains were cultivated for 30 days in 250mL of the same culture media. The crude extracts were obtained by partition with ethyl acetate. The extracts were sent for the cytotoxic activity bioassay and analyzed by thin layer chromatography (TLC) on silica gel plate (with absorption in UV-vis). Among the 26 extracts, samples DG (M3) 6'C and DG (M3) 5'C showed potent cytotoxic activity, samples DG (B) 13, DG (M3) 1 and DG (G) 2B a moderate activity. The analysis by TLC indicated the presence of bioactive secondary metabolites in the extracts. The strains were identified as bioactive three fungal: DG (M 3) 6'C (Penicillium sp.) DG (M3) 5'C (Cladosporium sp.) DG (M3) 1 (Aspergillus sp.) And two bacterial: DG (B) 13 (Aurantimonas sp.) DG (G) 2B (Nocardiopsis sp.). These were grown on a larger scale of broth (500 mL) and extracted after 7, 14, 21 and 30 days of incubation. We carried out a cleaning process of these extracts by solid phase extraction (SPE) column of silica gel derivatized with C18 (35 mL of eluent: 100% H2O, MeOH/H2O 1:1 and MeOH 100%). The fractions generated were analyzed by HPLC-UV-MS trying to find characteristic profiles of secondary metabolites. From the DG sample (M3) 6'C (A + B), was isolated and identified the compound 13- deoxy-fomenona previously obtained by Tirilly et al. in 1983. Although this compound is not unheard of, no literature reports of studies involving bioassays cytotoxic against tumor cells and even this compound has been isolated from other species of microorganisms other than the fungus Dicyma pulvinata.